Development of a PtSn bimetallic catalyst for direct fuel cells using bio-butanol fuel1. Issue 69 (7th September 2015) - Puthiyapura, V. K.; Brett, D. J. L.; Russell, A. E.; Lin, W. F.; Hardacre, C.
<x xml:space="preserve">Abstract</x> PtSn showed a higher activity and lower activation energy towards butanol electrooxidation compared to pure Pt.